Transgender viewed from the perspective of positive law, health, and cultures in Indonesia - Fifik Wiryani; Nurul Ummah; Mokhammad Najih; Muhammad Nasser; Nur Rohim Yunus (Legality : Jurnal Ilmiah Hukum, 2021)
Transgender people are seen as an abnormal minority group that bends the accepted sexual orientation against the cultures in Indonesia. This trend is also believed to be more prone to diseases. From the perspective of ius constitutum, transgender people are under different protection as set forth in Article 1 paragraph (3) of Law Number 39 of 1999 and Article 28 J of the 1945 Indonesian Constitution. However, the human rights governed are restricted to moral and religious, security, and public order rights. In the view of the positive law, in terms of health, every individual has the right to decide how they should live their life, but health is generally linked to diseases. When it comes to this matter, it can also be deemed inappropriate or deviant. Transgender people may be deprived of society, and they may have narrower room for their day-to-day activities such as mingling in religious activities and society, and even going to the restroom). This sexual tendency could also cause a serious disease like HIV/AIDS and irritate others due to their existence around them. In a different view, transgender people are recognized by the State that attempts to save them from conflicting thoughts of their existence. To conclude, being transgender is an inner disease existing in an individual. Although it is seen as normal by transgender people, this reality is still seen as discomfort by others.